EPISTEMOLOGI EKONOMI ISLAM DAN MAQASID SYARIAH DALAM KURIKULUM EKONOMI ISLAM DI PERGURUAN TINGGI - Selamat Muliadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2018)
Abstract. The Epistemology of Sharia Economy and Maqasid Sharia in Islamic Economics Curriculum in the Higher Education. The potencies and roles of Universities both Islamic Higher Education (PTA) and Public Higher Education (PTU) in providing human resources through Islamic economic and finance learning development that accommodates the competencies of industries demand. Islamic economic as discipline has foundation of epistemology. The main problem in the development of economic and Islamic finance in Indonesia is still the gap between the needs of industry and graduate from college. This study aims to analyze how epistemology and the development Islamic economic and curriculum structure of Islamic economics in universities that teach Islamic economic and what is effective approach to be applied so that graduates can meet the needs of financial industry Islamic economic. The method used in this study is a content analysis is used to explain the depth of the curriculum of Islamic economic in university. Based on the results of the study found that the difference was the presence of Islamic economic learning system in higher education so that graduates produced by universities that teach Islamic economic is still little that can meet the market needs of Islamic financial industry. Abstrak. Epistemologi Ekonomi Islam dan Maqasid Syariah Dalam Kurikulum Ekonomi Islam di Perguruan Tinggi. Potensi dan peran Universitas baik Pendidikan Tinggi Islam (PTA) dan Pendidikan Tinggi Publik (PTU) dalam menyediakan sumber daya manusia melalui pengembangan pembelajaran ekonomi dan keuangan Islam yang mengakomodasi kompetensi permintaan industri. Ekonomi Islam sebagai disiplin memiliki fondasi epistemologi. Masalah utama dalam pengembangan ekonomi dan keuangan Islam di Indonesia masih kesenjangan antara kebutuhan industri dan lulusan dari perguruan tinggi. Penelitian ini bertujuan untuk menganalisis bagaimana epistemologi dan pengembangan ekonomi Islam dan struktur kurikulum ekonomi Islam di universitas yang mengajarkan ekonomi Islam dan apa pendekatan yang efektif untuk diterapkan sehingga lulusan dapat memenuhi kebutuhan industri keuangan ekonomi Islam. Metode yang digunakan dalam penelitian ini adalah analisis isi yang digunakan untuk menjelaskan kedalaman kurikulum ekonomi Islam di universitas. Berdasarkan hasil penelitian ditemukan bahwa perbedaan itu adalah adanya sistem pembelajaran ekonomi Islam dalam pendidikan tinggi sehingga lulusan yang dihasilkan oleh perguruan tinggi yang mengajarkan ekonomi Islam masih sedikit yang dapat memenuhi kebutuhan pasar industri keuangan syariah